Bacterial Vaginosis - Abdul Karim; Jusuf Barakbah (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Bacterial vaginosis (BV) is the most common cause of vaginal discharge symptoms in reproductive women. BV is the most common cause of malodor of vaginal discharge and fluor albus, but 50% of BV patients give no symptoms. Purpose: To evaluate the general overview and management of new BV patients at the Sexual Transmitted Infection Division of Dermatology and Venereology Outpatient Clinic Dr. Soetomo General Hospital Surabaya from  the period of 2012-2014. Methods: A retrospective study was perfomed by evaluating medical records of new BV patients including basic data, history taking, examination, diagnosis, treatment, follow up, and counseling. Results: The overall number of new cases is 33. The majority age range 25-44 years old (57.6%) and 84.8% are married. The most main complaint is vaginal discharge without subjective complaints (42.4%), the most common type of complaint is recurrent ( 54.5%), the most sexual partners is husband (60.6%), usage history of vaginal douching (30.3%), the most vaginal discharge appearance is serous (75.8%), Whiff test positive and pH > 4.5 only 9.1% respectively. All microscopic preparation showed clue cell (100%). Therapy with metronidazole is given in 81.8%. Conclusion: The general overview of BV cases showed a small incidence with sexually active age group being the majority of cases and with the main complaint is vaginal discharge without other subjective complaint. The right management is needed to improve good service and reduce the recurrence rate.